Frozen Frontiers: Science Diplomacy and Antarctic Governance Where Technology Meets Global Cooperation (Prakriti - The International Multidisciplinary Research Journal, 2025)
The frozen and inhabited southernmost continent Antarctica, is an unparalleled example of global collaboration, sustainable environmental management, and collaborated scientific research. This research examines the pivotal role of science diplomacy within the Antarctic Treaty System, highlighting its contributions to fostering peaceful collaboration, addressing global environmental challenges, and advancing scientific knowledge. Through a detailed analysis of governance frameworks, technological innovations, and collaborative research initiatives, the study underscores how science diplomacy bridges geopolitical divides and promotes sustainable stewardship of Antarctica’s fragile ecosystem.As the impacts of climate change intensify, nations are compelled to adapt governance mechanisms to balance conservation with the strategic interests of state and non-state actors. The research also explores emerging challenges, including increased human activity, territorial ambitions, and the integration of artificial intelligence and digital monitoring technologies in environmental protection. By addressing these issues, the study provides actionable insights into enhancing international cooperation and ensuring the resilience of Antarctica as a global common. This work contributes to understanding how science-driven policies can safeguard one of the planet’s most critical regions while offering broader lessons for environmental governance in an interconnected world.
Keywords: Science Diplomacy; Antarctic Treaty System (ATS); Environment Governance; Climate Change, Geopolitics; Global Common